INCREASE STUDENT LEARNING ACTIVENESS AND CREATIVITY WITH ACTIVE LEARNING - Intan Fauzana; Neviyarni (Literasi Nusantara, 2021)
The development of the world of education now demands that students be active and creative in the learning process than their teachers. In the 2013 curriculum, it is explained that teachers become facilitators in teaching with more attractive methods/strategies, so that students are able to convey their opinions and thoughts. Activeness in learning is an effort to improve and optimize the student learning process so that they are involved intellectually and emotionally, and play an active role in learning. Then creativity in learning is the ability to create something new and different. However, at this time there were still students who were not active and creative in their learning, tending to accept everything the teacher said. So that students have low learning outcomes. Therefore, learning is needed to increase student activity and creativity in learning, namely active learning with the intention of empowering students to learn using various methods/strategies actively.